Rain fade prediction and diversity models for KU-band satellite in Malaysia - Lwas, Ali Khadim (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Tropical climate and equatorial climate experience heavy precipitation all over the year and Earth-to-satellite links that operate at frequencies higher than 10 GHz suffer from severe degradation of performance. In order to overcome such problems, link designers solely depend on prediction models most of which are developed based on measurements in temperate regions. Accurate estimation of rain attenuation leads to propose the appropriate and suitable mitigation technique for designing future high frequency Earth-to-satellite links. However available rain attenuation prediction models are unable to predict most of the measurements accurately in tropical regions. This research uses two years rain rate and rain attenuation data at Ku-band measured in Penang (4.390°N, 100.980°E), Malaysia for analyzing and developing rain attenuation prediction and mitigation techniques. Predictions by ITU-R and dual-layer models are analyzed using measured data and found unable to predict the measurements. Synthetic storm technique is also investigated and found neither measured rain attenuation nor duration is reflected with storm velocity in synthetic storm technique prediction in tropical regions. Dual-layer model is modified based on the concept of effective path length, rain rate variations along the slant path and the rain height model by considering either rain and melting layer or only rain layer. A control parameter rho is also introduced to represent the rain intensity variations along the satellite path. The value of the parameter is proposed based on measured data. The proposed model is validated using data measured in tropical climate of Malaysia and Philippine and found good agreement. The time diversity technique is investigated using one year measured rain fade and found very good improvement in system. Time diversity gain estimated from measured one-minute rain attenuation for one year period is utilized to develop a prediction model which can predict time diversity gain as a function of rain attenuation levels and time delay. Proposed model is validated using the measured data and found very good agreement. Site diversity technique is also analyzed using one year measurement in two locations separated by 37.36 km in Malaysia. It is found that 10 raining events occurred concurrently in both sites out of 381 measured events in a year and 0.000381% of outage probability can be achieved by considering highest 18 mm/hr rainfall rate for design. These findings will be useful tools for link designers to predict rain fade and apply time or site diversity as a rain fades mitigation technique in earth-satellite communications systems.